(untitled) (Baghdad Science Journal, 2025)
Three types of zeolite A were prepared from Iraqi kaoline which are 3A, 4A and 5A by ion exchange method .They were characterized by XRD and atomic absorption techniques .They were used as adsorbents to examine their applicability for H2S adsorption .The adsorption process was performed in a static form and constant volume system which constructed from stainless steel .The effect of zeolite type and temperature on the adsorption properties of H2S at -5 , 25 and 55 oC was studied .The zeolite type 5A has the highest adsorption value (79.384 µmol/g ) and the three types may be arranged in a sequence toward H2S adsorption as 5 A> 4A>3A .The amount of H2S adsorbed increased as temperature decreased from 55 to -5 for all samples. Langmuir , Frendlich and Toth isotherm equations model were applied for the adsorption data in order to determine the affinity and the heterogeneity of the three adsorbents. The heterogeneity parameters of the model equation applied indicated that 5A sample was more heterogeneous compared to other zeolite types.